Turning the tides: achieving rapid and safe glucose control in adolescents with suboptimally controlled type 1 diabetes using advanced hybrid closed loop systems - Castorani, Valeria; Rigamonti, Andrea; Frontino, Giulio; Morotti, Elisa; Sandullo, Federica; Scialabba, Francesco; Arrigoni, Francesca; Dionisi, Benedetta; Foglino, Riccardo; Morosini, Camilla; Olivieri, Gabriele; Bonfanti, Riccardo (Frontiers in Endocrinology, 2024)
Objective: This retrospective observational study assessed the Tandem Control IQ (CIQ) Advanced Hybrid Closed-Loop (AHCL) system's impact on adolescents with Type 1 Diabetes (T1D) exhibiting suboptimal glucose control due to poor treatment adherence. Methods: We evaluated 20 non-compliant T1D adolescents, previously reliant on Multiple Daily Injections (MDI) and flash glucose monitoring, who transitioned to the CIQ system. Key metrics like Time In Range (TIR), Time Above Range (TAR), mean glucose levels, and the Glucose Risk Index (GRI) were measured at baseline, 2 weeks, 1 month, and 6 months post-CIQ implementation. Results: The study involved 20 adolescents (average HbA1c: 10.0%±1.7). TIR improved from 27.1%±13.7 at baseline to 60.4%±13.3 at 6 months. TAR >250 mg/dL reduced from 46.1%±23.8 to 15.5%±10.5, and mean glucose levels dropped from 251 mg/dl±68.9 to 175mg/dl±25.5 over the same period. GRI significantly decreased from 102 to 48, and HbA1c improved to 7.0%±0.7 after 6 months. Notably, two patients experienced mild Diabetic Ketoacidosis (DKA) once. Discussion: AHCL systems, specifically CIQ, demonstrated a significant, rapid improvement in glucose control, indicating a pivotal advancement in technology for non-compliant adolescents. This study contributes new insights into AHCL's efficacy in this subgroup, showing considerable improvements in TIR, TAR, and overall glucose profiles from as early as two weeks after initiation. Limitations and Future Research: Despite its promising results, the study's limitations include a small sample size and lack of a control group. Further research with larger cohorts and extended follow-up is needed to substantiate these findings. Conclusion: The CIQ AHCL system markedly enhances glycemic control in non-compliant adolescents with T1D, suggesting its potential as a primary treatment modality for this challenging patient group. This study underlines AHCL technology's transformative impact, offering a path to better quality of life and reduced complications for adolescents with T1D.